2(n+3)-(4-6m)=7n

Simple and best practice solution for 2(n+3)-(4-6m)=7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(n+3)-(4-6m)=7n equation:


Simplifying
2(n + 3) + -1(4 + -6m) = 7n

Reorder the terms:
2(3 + n) + -1(4 + -6m) = 7n
(3 * 2 + n * 2) + -1(4 + -6m) = 7n
(6 + 2n) + -1(4 + -6m) = 7n
6 + 2n + (4 * -1 + -6m * -1) = 7n
6 + 2n + (-4 + 6m) = 7n

Reorder the terms:
6 + -4 + 6m + 2n = 7n

Combine like terms: 6 + -4 = 2
2 + 6m + 2n = 7n

Solving
2 + 6m + 2n = 7n

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + 6m + -2 + 2n = -2 + 7n

Reorder the terms:
2 + -2 + 6m + 2n = -2 + 7n

Combine like terms: 2 + -2 = 0
0 + 6m + 2n = -2 + 7n
6m + 2n = -2 + 7n

Add '-2n' to each side of the equation.
6m + 2n + -2n = -2 + 7n + -2n

Combine like terms: 2n + -2n = 0
6m + 0 = -2 + 7n + -2n
6m = -2 + 7n + -2n

Combine like terms: 7n + -2n = 5n
6m = -2 + 5n

Divide each side by '6'.
m = -0.3333333333 + 0.8333333333n

Simplifying
m = -0.3333333333 + 0.8333333333n

See similar equations:

| X-(1-3X)=2X-(-X-3) | | 7x+9=3x+33 | | 1.8=3y+16.5 | | 24y-2x=-1 | | 14.7+.445f=41.4 | | -4x+15= | | (2t^2+t+3)(4t^2+2t-2)=0 | | 9y-24=3(y-2) | | 6.50h+36.50=65.75 | | -6x-4y=-13 | | 14/-3 | | 2x+8=-2+44 | | 60=41x-5.5x^2 | | 60x=8x+20 | | 84/40 | | 4.9=-log(x) | | 4/5=1/4f | | 18x+y=28-3x | | (4x-9)(x)=90 | | S-9=12 | | log(3)(6x-3)=2 | | (12/5)(7/8) | | (5x-9)(x)=90 | | X^2+10x=-26 | | 3p/1-5/4p-14=0 | | -3z-7z=9z-5-7z | | 2/3-x/9 | | 176-16=0 | | 1d-11=-1(2d-7) | | (x+3)(x-9)-(-5x-7)(x-2)= | | y-23+x=0 | | (6/5)*(x-7)=0 |

Equations solver categories